Review of Factors Related to the Thyroid Cancer Epidemic. (7th May 2017) - Liu, Yihao; Su, Lei; Xiao, Haipeng
Abstract : Thyroid cancer is the most common endocrine cancer, of which the incidence has dramatically increased worldwide in the past few decades. The reasons for the observed rapid increase still are not fully understood, but evidence suggests that overdiagnosis, with the advancement in detection methods and screening policies, is not the sole driver of the substantial increase of the incidence. However, the effect of environmental/lifestyle factors remains speculative other than that of radiation exposure at a young age. This review tries to give a balanced view of debated factors leading to the thyroid cancer epidemic, to offer some alternatives in understanding the controversies, and to suggest potential directions in the search of modifiable risk factors to help reduce thyroid cancer.